PENGARUH LINGKUNGAN KERJA, TIPE KEPRIBADIAN, DAN GAYA KEPEMIMPINAN TERHADAP LOYALITAS KARYAWANPT. SANDABI INDAH LESTARI BENGKULU UTARA - Vika Fikuria; Adi Sismanto ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
This study aims to determine the effect of the work environment, personality type and leadership style on employee loyalty at PT. Sandabi Indah Lestari. This type of research is a type of quantitative research, the object of this research is all permanent employees in the factory office area of ​​PT Sandabi Indah Lestari. Sampling method using total sampling technique. The number of respondents in this study were 126 people. Methods of data collection using a questionnaire. The data analysis technique uses Multiple Linear Regression Analysis Test, and Hypothesis Testing, namely t-test and F-test. The results of this study can be concluded that the work environment variable has a positive effect on employee work loyalty, personality type has a positive effect on employee work loyalty, and leadership style has a positive effect on employee work loyalty. Keywords: work environment, personality type and leadership style on employee loyalty